A Novel Approach for Intruder Localization Based on Leaky Coaxial Cable Sensor with IQ Demodulation and Synchronous Subtraction - Qiao Guan; Hongmin Lu; Kunbo Wang; Chongchong Chen, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Some aspects of the intruder detection system (IDS) based on the leaky coaxial cable (LCX) sensor are still unknown due to its complex propagation characteristics. In order to study the field disturbance mechanism of human intruder and to reduce the phase error caused by the initial state of the detection signal, a novel method of improving the localization accuracy is proposed. At the frequencies of 40MHz, 100MHz and 200MHz, the IDS based on the LCX sensor is proposed by analyzing the scattering characteristics of human intruder and using IQ demodulation method. According to the characteristics of the IDS, the electric field distribution is obtained by irradiating the human intruder from three typical radiation directions, which are front, side and low-side direction in the mentioned frequency range. Combined with the method of pulse accumulation and synchronous subtraction, the intruder localization can be easily realized by using pulse delay positioning method. The results demonstrate the improvement in localization accuracy and the decrement in false positive rate, and the positioning accuracy is less than 3 meter.